A new Endoclita (C. &. R. Felder, 1874) from the High Mountains of Taiwan with notes about its evolutionary origins (Lepidoptera: Hepialidae) - Buchsbaum, Ulf; Hsu, Li-Peng; Chen, Ding-Jia; Grehan, John R. (Zootaxa, 2018)
A new species Endoclita atayala Buchsbaum & Hsu sp. n. is based on a single female specimen collected at light in the high mountains of northern Taiwan. Comparisons with all other Endoclita (C. & R. Felder, 1874) species confirms that E. atayala sp. n. exhibits distinctive and unique wing pattern characteristics and probably has a sister group relationship with E. crenilimbata (Le Cerf, 1919) of southeastern China and illustrated here for the first time, and E. nodus (Chu & Wang, 1985) of northeastern China. The species diversity of Taiwanese Hepialidae is described and the biogeographic implications of the E. atayala sp. n. relationship for the origin of endemic species in Taiwan are reviewed.